Cyclooxygenase-2 contributes to the selective induction of cell death by the endocannabinoid 2-arachidonoyl glycerol in hepatic stellate cells - Siegmund, Sören Volker; Singer, Manfred V. (Biochemical and biophysical research communications, 2016)
The endogenous cannabinoid 2-arachidonoyl glycerol (2-AG) is an anti-fibrotic lipid mediator that induces apoptosis in hepatic stellate cells (HSCs), but not in hepatocytes. However, the exact molecular mechanisms of this selective induction of HSC death are still unresolved. Interestingly, the inducible isoform of cyclooxygenase, COX-2, can metabolize 2-AG to pro-apoptotic prostaglandin glycerol esters (PG-GEs). We analyzed the roles of COX-2 and endocannabinoid-derived PG-GEs in the differential susceptibility of primary activated HSCs and hepatocytes toward 2-AG-induced cell death. HSCs displayed significant COX-2 expression in contrast to hepatocytes. Similar to 2-AG, treatment of HSCs with PGD2-GE dose-dependently induced cell death independently from cannabinoid receptors that was accompanied by PARP- and caspase 3-cleavage. In contrast to 2-AG, PGD2-GE failed to induce significant ROS formation in HSCs, and depletion of membrane cholesterol did not rescue HSCs from PGD2-GE-induced apoptosis. These findings indicate differential engagement of initial intracellular signaling pathways by 2-AG and its COX-2-derived metabolite PGD2-GE, but similar final cell death pathways. Other PG-GEs, such as PGE2-or PGF2α-GE did not induce apoptosis in HSCs. Primary rat hepatocytes were mainly resistant against 2-AG- and PGD2-GE-induced apoptosis. HSCs, but not hepatocytes were able to metabolize 2-AG to PGD2-GE. As a proof of principle, HSCs from COX-2-/- mice lacked PDG2-GE production after 2-AG treatment. Accordingly, COX-2-/- HSCs were resistant against 2-AG-induced apoptosis. In conclusion, the divergent expression of COX-2 in HSCs and hepatocytes contributes to the different susceptibility of these cell types towards 2-AG-induced cell death due to the generation of pro-apoptotic PGD2-GE by COX-2 in HSCs. Modulation of COX-2-driven metabolization of 2-AG may provide a novel physiological concept allowing the specific targeting of HSCs in liver fibrosis.